Transfer pricing: Dampak beban pajak dan tunneling incentive pada perusahaan multinasional - Afif Umar Suryo; Amelia Oktrivina; Susilawati Susilawati (LPMP Imperium, 2026)
This study aims to analyze the effect of Tax Burden and Tunneling Incentive on Transfer Pricing practices, with Company Size and Profitability as control variables. The research population comprises multinational companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX). The purposive sampling method was applied, resulting in a final sample of 11 companies observed over the 2019–2023 period, yielding 55 panel data observations. The analysis was conducted using panel data regression analysis with the Fixed Effect Model in SPSS 25. The results indicate that, partially, neither Tax Burden nor Tunneling Incentive has a significant effect on Transfer Pricing. This finding suggests that, within the specific context of post-BEPS regulatory strengthening in Indonesia, traditional motives of fiscal burden and shareholder expropriation do not directly drive aggressive transfer pricing strategies among the sampled companies. The study implies that enhanced regulatory frameworks and corporate governance may have altered corporate decision-making calculus. Public Interest Statement This research highlights the potential effectiveness of strengthened international tax regulations (BEPS) and domestic oversight in curbing aggressive transfer pricing motivated by simple tax savings or tunneling. The findings encourage regulators to maintain and enhance transparent reporting requirements and robust enforcement.